2016
DOI: 10.1099/jgv.0.000593
|View full text |Cite
|
Sign up to set email alerts
|

Replication of Merkel cell polyomavirus induces reorganization of promyelocytic leukemia nuclear bodies

Abstract: Merkel cell polyomavirus (MCPyV) is associated with Merkel cell carcinoma (MCC), a rare but aggressive skin cancer. The virus is highly prevalent: 60-80 % of adults are seropositive; however, cells permissive for MCPyV infection are unknown. Consequently, very little information about the MCPyV life cycle is available. Until recently, MCPyV replication could only be studied using a semi-permissive in vitro replication system (Neumann et al., 2011; Feng et al., 2011, Schowalter et al., 2011). MCPyV replication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Kap1 depletion increases MCPyV DNA replication. To evaluate the consequences of Kap1/T protein interaction, we performed MCPyV DNA replication assays using a semipermissive system (12,15,16,35,36) in cells positive or negative for Kap1 expression. We generated HEK293 cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kap1 depletion increases MCPyV DNA replication. To evaluate the consequences of Kap1/T protein interaction, we performed MCPyV DNA replication assays using a semipermissive system (12,15,16,35,36) in cells positive or negative for Kap1 expression. We generated HEK293 cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MCPyV replication assay. In vitro replication assays were performed as previously described (15,16,35). For nHDF cells, 1 ϫ 10 6 cells were transfected with 2 g MCVSyn or pUC18 plasmid (mock) using electroporation.…”
Section: Methodsmentioning
confidence: 99%
“…While our RNA-seq data identified various cellular targets, many of which are involved in immune-related processes, it is important to acknowledge that given the HEK293-cell background, it is possible that some relevant targets were missed. SP100 is an intriguing MCV-miR-M1 target, which has been implicated in the innate immune response against double-stranded DNA viruses, including MCPyV (Gunther et al, 2014;Jiang et al, 2011;Neumann et al, 2016;Tavalai and Stamminger, 2009;Wagenknecht et al, 2015) and has been shown to be down-regulated during MCPyV replication, although no mechanism for this was reported (Neumann et al, 2016). Our data suggest that MCV-miR-M1 mediates, at least in part, the observed down-regulation of SP100 in cells harboring synthetic MCPyV.…”
Section: Discussionmentioning
confidence: 76%
“…In the maturation process they hydrolyse a peptide bond close to the C-terminus of SUMO precursors, eliminating the very C-terminal amino acids from SUMO1, SUMO2 and SUMO3 and exposing two glycine residues. In SUMO1-3, the diGly motif is preceded by a glutamine (Q) and threonine (T), while SUMO4 exhibits a PTGG motif, in which the proline residue confers resistance to SENPmediated cleavage (Owerbach et al, 2005). In the deconjugation process, SENPs cleave an isopeptide bond that links SUMO moieties to the ε-amino group of lysine residues.…”
Section: Senpsmentioning
confidence: 99%
“…MCPyV transforming ability mainly resides on the expression of Large T antigen proteins (Large-LT, and Short-ST) (Houben et al, 2010), even if molecular details driving MCPyV-mediated cell transformation are still not fully elucidated, although a role for ST is emerging (Shuda et al, 2011). Similarly, a role for viral exploitation of the SUMO pathway during Merkel cell carcinoma has not yet been investigated, even if a recent report shows that MCPyV replication depends on PML-NBs, suggesting a possible involvement of SUMOylation in regulating MCPyV transformation (Neumann et al, 2016).…”
Section: Epstein-barr Virusmentioning
confidence: 99%